(untitled) (American International Journal of Sciences and Engineering Research, 2022)
Although the construction industry has been evolving for centuries and researchers have been seeking innovative solutions for decades, diverse challenges still exist in making the construction process faster, safer, cheaper, and more accurate. Building Information Modelling (BIM) is one of the emerging tools in the field of architectural engineering to overcome these problems. Applications of this tool are very promising but its uses are still relatively limited in many countries including Bangladesh. So this study conducted a pilot project and case study analysis using Building Information Modeling (BIM) to control the project’s time and cost from Bangladesh’s perspective. The objectives of this study are: (1) to examine the benefits of using BIM for project time and cost control and (2) to study the challenges of applying BIM to a case project during its life cycle. This project is being achieved by introducing Autodesk Revit MEP (2021) as the methodological tool of BIM software. The resultant data in the BIM system are extremely useful and can be generated to optimize the project delivery processes. The results also revealed that using a case study, BIM functions to help reduce costs, optimise the schedule, and make benefits for all project participants. Thus, model-based cost estimation and time schedule optimization show effective results of using BIM instead of conventional modelling methods. JEL Classification Codes: C60, L74, R20, R30